Palm oil industry effect on water quality status of Pawan and Jelai Rivers in Ketapang Regency in 2012-2016 - Mohamad Rusdi Hidayat; Agus Sri Mulyono (Brawijaya University, 2019)
Pawan and Jelai Rivers are two of the three main rivers in Ketapang Regency, West Kalimantan. The extensive growth of palm oil industry in Ketapang might affect the aquatic environment, especially the rivers, due to excessive uses of water. Therefore, the aims of this study were to examine the effect of palm oil industry on the changes in water quality status of Pawan and Jelai Rivers in Ketapang regency during 2012-2016 and to identify critical parameters that might determine the water quality status in the two rivers. This study used the laboratory testing results of Pawan and Jelai Rivers, which were carried out periodically by various companies/institutions. There were 24 physical, chemical, and microbiological parameters that were analyzed to determine the water quality status using STORET method. Critical parameters were determined by comparing parameters analyzed with their threshold values. The results revealed that Pawan and Jelai Rivers passing through oil palm plantations and palm oil mills were moderately to highly polluted in 2012, 2014 and 2016. Critical parameters of the river water quality are BOD, COD, Cl2, phenol, Fe, and total Coliform.